Hepatic incidentaloma: An asymptomatic ectopic thyroid tissue - Di Stefano, Claudia; Guarnotta, Valentina; Barbaccia, Maria; Paratore, Rosario; La Monica, Roberta; Lo Casto, Antonio; Midiri, Massimo; Gruttadauria, Salvatore; Giordano, Carla; Richiusa, Pierina (Frontiers in Endocrinology, 2022)
An ectopic thyroid is a form of thyroid dysgenesis in which an entire or parts of the thyroid gland may be located in another part of the body than what is the usual place. The most frequent location is the base of tongue. Although most cases are asymptomatic, symptoms related to tumor size and its relationship with surrounding tissues, hormonal dysfunction and seldom malignancy may also occur. Here we describe the case of an asymptomatic woman who was thyroidectomized 19 years previously for a toxic goiter and treated with conventional L-thyroxine therapy, until we enacted a progressive reduction of dosage of the replacement therapy, and incidentally because of occasional abdomen discomfort was hospitalized in our division of Endocrinology because there was ultrasound evidence of a large mass in the liver dislocating and imprinting the choledochal duct in the pre-pancreatic site, the gallbladder and the cystic duct, which could not be dissociated from the contiguous hepatic parenchyma and was in very close proximity to the second duodenal portion and the head of the pancreas. Imaging techniques, such as TC, MR, TC/PET and 131I scintigraphy, confirmed the large lesion with a diameter on the axial plane of about 8 x 5.5 cm and a cranio-caudal extension of about 6 cm. The impossibility of surgical debulking and/or radiometabolic 131I-therapy, in the absence of compression symptoms, led to the multidisciplinary decision of a clinical and instrumental follow-up of this rare lesion.